Coregistration of fNIRS data on to the realistic head model - Emir, U; Duru, A; Ademoglu, A; Akin, A (2005)
In this paper, we propose a method to visualize fNIRS(Functional Near Infrared Spectroscopy) data on a realistic head model. In order to illustrate the success of this study, we used fNIRS data obtained during the Stroop task. For the realistic head model, high resolution T1 weighted MR images are used. Preliminary results show that proposed method will be usefull for visualization of fNIRS data and also these results are correlated with EEG (Electroencephalogram) topograpghic mapping for the same Stroop Task. ©2005 IEEE.